DESIGN OF WIRELESS POINT TO POINT NETWORK IN SERIGENI NEW VILLAGE, KAB. OGAN KOMERING ILIR - Yosi Pratama (International Journal Cister, 2022)
The technology that is developing at this time can certainly make it easier and maximize in doing various things in daily life, including in terms of accessing various information and data using an internet network media so that we can access data and information from outside with ease. The computer network project then began to feel the benefits. When a computer network is created, everyone can work more optimally and can do many processes without wasting a lot of time. The results of the computer network project then produce a program called Batch Processing (continuous process). This program allows multiple users to use multiple computers to work on multiple programs and jobs at the same time. The existence of technology helps humans in solving various problems in everyday life to get fast, precise and accurate information. Packet Tracer is a simulator of Cisco network tools that is often used as a medium of learning and training, and also in the field of computer network simulation research. Packet Tracer is usually used by Cisco Networking Academy students through Cisco Certified Network Associate (CCNA) certification. The function of the Packet Tracer is to design a system or network topology that will be applied to the real world / work, because if we design a computer network topology without the help of an application like this, it can be expensive. That's why Cisco made an application like this so that people can learn without the need for expensive fees. To overcome these problemsThe technology that is developing at this time can certainly make it easier and maximize in doing various things in daily life, including in terms of accessing various information and data using an internet network media so that we can access data and information from outside with ease. The computer network project then began to feel the benefits. When a computer network is created, everyone can work more optimally and can do many processes without wasting a lot of time. The results of the computer network project then produce a program called Batch Processing (continuous process). This program allows multiple users to use multiple computers to work on multiple programs and jobs at the same time. The existence of technology helps humans in solving various problems in everyday life to get fast, precise and accurate information. Packet Tracer is a simulator of Cisco network tools that is often used as a medium of learning and training, and also in the field of computer network simulation research. Packet Tracer is usually used by Cisco Networking Academy students through Cisco Certified Network Associate (CCNA) certification. The function of the Packet Tracer is to design a system or network topology that will be applied to the real world / work, because if we design a computer network topology without the help of an application like this, it can be expensive. That's why Cisco made an application like this so that people can learn without the need for expensive fees. To overcome these problems